2010
DOI: 10.1371/journal.pntd.0000841
|View full text |Cite
|
Sign up to set email alerts
|

TcTASV: A Novel Protein Family in Trypanosoma cruzi Identified from a Subtractive Trypomastigote cDNA Library

Abstract: BackgroundThe identification and characterization of antigens expressed in Trypanosoma cruzi stages that parasitize mammals are essential steps for the development of new vaccines and diagnostics. Genes that are preferentially expressed in trypomastigotes may be involved in key processes that define the biology of trypomastigotes, like cell invasion and immune system evasion.Methodology/Principal FindingsWith the initial aim of identifying trypomastigote-specific expressed tags, we constructed and sequenced an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 53 publications
0
39
0
1
Order By: Relevance
“…Much of the genome of T. cruzi is composed of repeated elements, among which the following multigene surface families are found: TS, mucin, MASP, dispersed gene family-1, gp63, TcTSAV or TcSMP 18 39 40 41 . The antigenicity of proteins belonging to the TS and mucin families has been previously described, and recent reports showed that peptides from the hypervariable MASP region could elicit IgM and IgG responses in experimental infections 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Much of the genome of T. cruzi is composed of repeated elements, among which the following multigene surface families are found: TS, mucin, MASP, dispersed gene family-1, gp63, TcTSAV or TcSMP 18 39 40 41 . The antigenicity of proteins belonging to the TS and mucin families has been previously described, and recent reports showed that peptides from the hypervariable MASP region could elicit IgM and IgG responses in experimental infections 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Peptides from the same protein were synthesized at randomized positions within a single sector. The chip contains additional 2386 unique peptides corresponding to eight proteins not accounted within the protein groups defined above (and of which 2 proteins resulted seropositive), including members of the T. cruzi TASV protein family ( 30 , 31 ) and 21 epitopes of high prevalence in healthy humans (not associated to Chagas disease, identified in the IEDB with a search for linear B-cell epitopes from any source with sero-prevalence > = 50%, assayed in at least 20 subjects). The sequences of these 532 proteins (457 T. cruzi proteins, 54 neo-proteins and the additional 21 short peptidic epitopes of high prevalence in healthy humans) are available in supplemental Table S4 .…”
Section: Methodsmentioning
confidence: 99%
“…54 Similarly, a novel family of surface proteins has been recently identified that seems to be specific for T. cruzi. 55 Taken together, these studies may thus lead to some promising antigens with important potential as novel vaccine candidates.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 98%